Modeling of wave propagation in a geomedium layer using PML absorbing boundary conditions - Bakeev, R. A. (AIP conference proceedings, 2019)
To solve dynamic problems of the geomechanics in the Earth’s crust requires numerical modeling algorithms for the elastic wave propagation in a semi-infinite medium. Due to the limited computing resources, absorbing boundary conditions are an important component of such algorithms. In the present work, the perfectly matched layer (PML) method is adapted for the finite-difference method for solving dynamic and quasi-static problems of geomechanics in the field of gravity. The finite-difference analogues of the motion and constitutive equations are modified. Test results on the elastic wave propagation are presented.